The Influence of Service Quality and Trust on Customer Satisfaction: (A Study at PT. Bank Perkreditan Rakyat Surasari Hutama Sukorejo Branch, Pasuruan Regency) - Solikha, Fitriatus; Zunaida, Daris; Eny, Eny (CV. Proaksara Global Transeduka, 2024)
The primary objective of this research is to identify and examine how service quality impacts customer satisfaction. To understand and analyze the relationship between trust and customer satisfaction. To explore and analyze the simultaneous and partial impact of service quality and customer satisfaction guarantees. A quantitative research approach was applied in this kind of research. The recorded review approach used a sample of 115 participants. According to the evaluation findings, customer satisfaction is positively and significantly influenced by service quality (X1), as evidenced by a t-calculated score greater than the t-table score (4.196 > 1.981) and a significance level below 0.05 (0.000 < 0.05). Additionally, customer satisfaction regarding the F-test value is influenced by both service quality and trust, determined by an F-table score greater than the F-calculated score (165.263 > 3.08) and a significance level of F below 0.05 (0.000 < 0.05). The adjusted R-square score of 0.742, also known as the coefficient of determination (R2), indicates that the total contribution of all X variables, namely trust and service quality, to the Y variable, which is customer satisfaction, is 74.2%. The remaining 25.8% is attributed to other factors not covered in this research.